Mental Accounting Etnis Minoritas Berbasis Mali Siparappe Rebba Sipatokkong Malilu Sipakainge di Teluk Tomini - Amaliah, Tri Handayani; Musdalifah, Musdalifah; Anwar, Mohamad Sultan; Hemeto, Inul (Al-Buhuts, 2024)
This study aims to explore  the culture-based mental accounting  behavior of mali siparappe rebba sipatokkong malilu sipakainge in ethnic minorities (Bugis) in Tomini Bay. This research is in the realm of qualitative research with an interpretive paradigm. The method used is ethnomethodology. Data collection was conducted through observation and interviews. The informants in this study consist of ethnic minorities in Gorontalo City, namely Bugis entrepreneurs, and academics. The results of the study show that the mental accounting framework in the Bugis ethnicity based on the Mali siparappe rebba sipatokkong malilu sipakainge culture plays a role in advancing MSMEs in Tomini Bay. The mental accounting of the Bugis ethnic minority shows a pattern of mental allocation strategy, which prioritizes stable cash flow to maintain business sustainability rather than momentary gains. Spiritual strength, social values and hard work in the mental category are important investments to achieve success in business. Mental accounting in the Bugis ethnicity can be seen through the way Bugis business people classify and assess profits that go beyond the traditional financial framework. The implications of this study provide an understanding of the integration of local culture in accounting practices, especially financial behavior to advance MSMEs